2005
DOI: 10.1016/j.virol.2005.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular route and biological activity of exogenously delivered Rep proteins from the adeno-associated virus type 2

Abstract: The two large Rep proteins, Rep78 and Rep68, from the adeno-associated virus type 2 (AAV-2) are required for AAV-2 DNA replication, site-specific integration, and for the regulation of viral gene expression. The study of their activities is dependent on the ability to deliver these proteins to the cells in a time and dose-dependent manner. We evaluated the ability of a protein transduction domain (PTD) derived from the human immunodeficiency virus 1 (HIV-1) TAT protein to drive the cellular internalization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…We hypothesized that infectious AAV8ΔVP1 particles could be explained by the relatively high AAV multiplicity used and the presence of Ad, known to be an intracellular carrier for various biological molecules, especially through its endosomolytic activity. 29 , 30 Thus, the high Ad multiplicity (500 IUs/cell) used in the TCID 50 and ICA may help non-infectious AAV particles to escape the endosomes and reach the cell nucleus. Importantly, in the case of AAV8ΔVP1, the difference in the VG:IU ratio calculated with the TCID 50 (2.9 × 10 3 ) was about 4-log 10 higher compared to that calculated with the ICA (3.1 × 10 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that infectious AAV8ΔVP1 particles could be explained by the relatively high AAV multiplicity used and the presence of Ad, known to be an intracellular carrier for various biological molecules, especially through its endosomolytic activity. 29 , 30 Thus, the high Ad multiplicity (500 IUs/cell) used in the TCID 50 and ICA may help non-infectious AAV particles to escape the endosomes and reach the cell nucleus. Importantly, in the case of AAV8ΔVP1, the difference in the VG:IU ratio calculated with the TCID 50 (2.9 × 10 3 ) was about 4-log 10 higher compared to that calculated with the ICA (3.1 × 10 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…To this end, for all samples prepared by procedures 1–4, protease inhibitors (Complete Protease Inhibitor Cocktail, Roche) were added and samples underwent 3 freeze/thaw cycles to disrupt membranes. Purified His-tagged Rep68 protein (500 ng) 30 was then spiked in each sample, before the addition of 4 sample volumes of ice-cold acetone and overnight precipitation at −20°C. Proteins were then pelleted at 16,000 × g for 15 min at 4°C and resuspended in 150 μL of 1× Laemmli buffer.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro evidences have suggested that Tat/PTD-fusion proteins or Tat peptides enter via an energy-dependent endocytotic (including caveolae) process [110][111][112][113][114], because the membrane inhibitor sodium azide inhibits ATP production and impairs endocytosis [115,116]. Further, protein transduction was strongly inhibited by energy depletion in cells at low temperature [110,112].…”
Section: Mechanism Of Ptd Internalizationmentioning
confidence: 99%
“…[242][243][244][245] Here it was subsequently shown that several recombinaseswhich incidentally are cationic proteins-actually contain innate membrane-translocation properties. [246][247][248] Several accounts have now appeared where attempts were made to compare the delivery efficiency of various vectors (e.g., Refs. 249,250).…”
Section: Delivery Efficiencymentioning
confidence: 99%